2020
DOI: 10.21467/ias.9.1.100-110
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wood Ash as Additive for Cow Manure Composting

Abstract: A B S T R A C TThis study was conducted to produce high-quality compost using both cow manure and wood ash that can specifically be used to increase the fertility of soils in tropical regions. Increased proportions of wood ash were co-composted with cow manure. During composting, the composts produced presented the classical composting temperature curve and attain a thermophilic composting phase (about 60 o C). After 117 days of composting, the produced composts (CMA 0%; CMA 5%; CMA 10% and CMA15%) had a C/N r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…The salinity of a compost is measured by its electrical conductivity, which greatly depends on the nutrient content of the compost and determines the phytotoxicity of a compost. Therefore, the increase of EC regarding the amount of cassava peels, which was composted, could be explained by the process of organic matter mineralisation, which always takes place during the composting process [21] [22]. That increase might also be the result of the maturation phase, which is the last phase of the process of composting, during which there is a production of organic acids and soluble salt.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The salinity of a compost is measured by its electrical conductivity, which greatly depends on the nutrient content of the compost and determines the phytotoxicity of a compost. Therefore, the increase of EC regarding the amount of cassava peels, which was composted, could be explained by the process of organic matter mineralisation, which always takes place during the composting process [21] [22]. That increase might also be the result of the maturation phase, which is the last phase of the process of composting, during which there is a production of organic acids and soluble salt.…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
“…Moreover, it could also be explained by the slight amount of Mg 2+ ; Ca 2+ ; K + and Na + in the produced composts. [22] [23] [24]. As a result, a great amount of cassava peels might increase the salinity of the final product that might cause osmotic problems and affects water intake ability [22].…”
Section: Physical and Chemical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of these materials in the process of The impact of the addition of natural materials on the composting of animal manure storage and composting of organic substrates results in better utilization of nutrients, reduction of risk of leakage of pollutants, especially nitrogen and phosphorus, into soil and water as well as reduction of contamination of individual environmental compartments by microorganisms (Sasáková, 2015). Bougnom et al (2020) reported, that the co-composting of cow manure with wood ash (<15%) allowed the authors to obtain a good organic fertilizer with higher liming potential and nutrient content.…”
Section: Introductionmentioning
confidence: 99%